Applying Modeling and Simulations for Rational Dose Selection of Novel Toll‐Like Receptor 7/8 Inhibitor Enpatoran for Indications of High Medical Need. Issue 2 (21st May 2022) - Klopp‐Schulze, Lena; Shaw, Jamie V.; Dong, Jennifer Q.; Khandelwal, Akash; Vazquez‐Mateo, Cristina; Goteti, Kosalaram
Abstract : Dual toll‐like receptor (TLR) 7 and TLR8 inhibitor enpatoran is under investigation as a treatment for lupus and coronavirus disease 2019 (COVID‐19) pneumonia. Population pharmacokinetic/pharmacodynamic (PopPK/PD) model‐based simulations, using PK and PD (inhibition of ex vivo ‐stimulated interleukin‐6 (IL‐6) and interferon‐α (IFN‐α) secretion) data from a phase I study of enpatoran in healthy participants, were leveraged to inform dose selection for lupus and repurposed for accelerated development in COVID‐19. A two‐compartment PK model was linked to sigmoidal maximum effect (Emax ) models with proportional decrease from baseline characterizing the PD responses across the investigated single and multiple doses, up to 200 mg daily for 14 days ( n  = 72). Concentrations that maintain 50/60/90% inhibition (IC50/60/90 ) of cytokine secretion (IL‐6/IFN‐α) over 24 hours were estimated and stochastic simulations performed to assess target coverage under different dosing regimens. Simulations suggested investigating 25, 50, and 100 mg enpatoran twice daily (b.i.d.) to explore the anticipated therapeutic dose range for lupus. With 25 mg b.i.d., > 50% of subjects are expected to achieve 60% inhibition of IL‐6. With 100 mg b.i.d., most subjects are expected to maintain almost complete target coverage for 24 hours (> 80% subjects IC90, IL‐6  = 15.5 ng/mL; > 60% subjects IC90, IFN‐α  = 22.1 ng/mL). For COVID‐19, 50 and 100 mg enpatoran b.i.d. were recommended; 50 mg b.i.d. provides shorter IFN‐α inhibition (median time above IC90  = 13 hours/day), which may be beneficial to avoid interference with the antiviral immune response. Utilization of PopPK/PD models initially developed for lupus enabled informed dose selection for the accelerated development of enpatoran in COVID‐19.